IMPLEMENTATION OF INTEGRATED TERRITORIAL INVESTMENTS IN POLAND – RATIONALE, RESULTS, AND RECOMMENDATIONS - Kociuba, Dagmara (Quaestiones Geographicae, 2018)
The objective of the article is the presentation of the practical aspect of implementation of one of the new tools of Cohesion Policy 2014–2020, namely Integrated Territorial Investments (ITIs) in functional urban areas (FUAs) in Poland. In the context of general rules of implementation of the instrument resulting from statutory provisions and ministry guidelines, the article presents the practical aspects of that process, including the establishment of an ITI union, the delimitation of the support area, development of the ITI strategy, and thematic and substantive scope of projects designated for financing. Moreover, the paper presents the degree of advancement of the implementation of ITIs as at the end of May 2018. The analyses permitted the identification of areas that will receive the most support and development of a catalogue of predominant investments and their beneficiaries, as well as a level of contracting of dedicated allocation of ITIs in particular FUAs. Finally, the article includes recommendations of what should be changed in the institutional, governance, and strategic programming aspect for the implementation of ITIs in the future perspective to be more effective.